2008
DOI: 10.1007/s11418-008-0244-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant constituents in the dayflower (Commelina communis L.) and their α-glucosidase-inhibitory activity

Abstract: The dayflower, Commelina communis L., contains 1-deoxynojirimycin (DNJ) and (2R,3R,4R,5R)2,5-bis(hydroxymethyl)-3,4-dihydroxypyrrolidine (DMDP), potent alpha-glucosidase inhibitors. The extracts and powder of this herb are important food materials for prophylaxis against type 2 diabetes. Eleven flavonoid glycosides as antioxidants, isoquercitrin, isorhamnetin-3-O-rutinoside, isorhamnetin-3-O-beta-D-glucoside, glucoluteolin, chrysoriol-7-O-beta-D-glucoside, orientin, vitexin, isoorientin, isovitexin, swertisin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
69
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(83 citation statements)
references
References 15 publications
7
69
1
3
Order By: Relevance
“…Narcissin, however, was reported to be inactive (Robak et al, 1988). Of the flavonoids, only rutin showed high activity as a-glucosidase inhibitor, in accordance with previous investigations (De Souza Schmidt Goncalves et al, 2010;Shibano et al, 2008). Due to the lack of material, the highest measured concentration for narcissin was 6.3 mM, so it may be that narcissin may have activity toward a-glucosidase at higher concentrations.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Narcissin, however, was reported to be inactive (Robak et al, 1988). Of the flavonoids, only rutin showed high activity as a-glucosidase inhibitor, in accordance with previous investigations (De Souza Schmidt Goncalves et al, 2010;Shibano et al, 2008). Due to the lack of material, the highest measured concentration for narcissin was 6.3 mM, so it may be that narcissin may have activity toward a-glucosidase at higher concentrations.…”
Section: Resultssupporting
confidence: 90%
“…Due to the lack of material, the highest measured concentration for narcissin was 6.3 mM, so it may be that narcissin may have activity toward a-glucosidase at higher concentrations. A previous investigation (Shibano et al, 2008) reported an IC 50 value for narcissin of 510 mM. Chebulic acid trimethyl ester, a novel compound previously isolated by us (Pham et al, 2011b), was found to have good 15-LO inhibitory activity, but was inactive as a-glucosidase inhibitor at the highest measured concentration (50 mM).…”
Section: Resultsmentioning
confidence: 83%
“…Previous reports have shown that polysaccharides from a wide range of food or medical plant sources could be effective α-glucosidase inhibitors (Kwon et al, 2008;Shibano et al, 2008;Kim et al, 2010). In this study, the inhibitory effects of TFPPs on α-glucosidase were investigated.…”
Section: Resultsmentioning
confidence: 98%
“…Extracts from various plants such guava leaves (Deguchi and Miyazaki, 2010), Salacia reticulate (Yoshino et al, 2009), and mulberry leaves (Asano et al, 2001;Park et al, 2009) have been shown to inhibit α-glucosidase activity, often with the involvement of polyphenols. Isoquercitrin, which was isolated from dayflower (Commelina communis L.), was found to be a component that inhibits α-glucosidases with potency close to that of 1-deoxynojirimycin, a potent α-glucosidase inhibitor (Shibano et al, 2008). In rats with alloxan-induced type 1 diabetes mellitus, isoquercitrin is known to decrease fasting blood glucose levels and to improve diabetes mellitus by reducing insulin synthesis and/or secretion, and/or by suppressing G6Pase activity (Panda and Kar, 2007).…”
Section: Con Q3gmentioning
confidence: 99%